2020
DOI: 10.3390/fermentation6040099
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Bioethanol Plant By-Product Valorization: Exploring Market Opportunities with Protein-Rich Fungal Biomass Production

Abstract: The feasibility of dry-grind bioethanol plants is extremely dependent on selling prices of ethanol and by-products, known as Dried distillers grains with solubles (DDGS), and sold as animal feed. Increasing the amount and quality of the by-products can widen potential feed and food markets and improve the process economy and robustness to price fluctuations of ethanol and grain. In this study, the techno-economic analysis of a bioethanol plant was investigated. Integration of edible filamentous fungi into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
0
3
0
2
Order By: Relevance
“…It should also be noted the original intent of the Rank Hovis McDougal Research Centre was to convert the waste starch product into a protein-rich food, however this determined to be not feasible due to technical/economic limitations related to starch uptake and conversion (Whittaker et al, 2020). Other recent mycoprotein have focused on a single feedstock from agriculture/food production co-products or waste streams which is highly valuable but provides less flexibility than our model (Ritchie et al, 2017;Bulkan et al, 2020;Upcraft et al, 2021). Our model TEA developed a flexible and open access model with the ability to change feedstock composition as innovation occurs in the alternative protein space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted the original intent of the Rank Hovis McDougal Research Centre was to convert the waste starch product into a protein-rich food, however this determined to be not feasible due to technical/economic limitations related to starch uptake and conversion (Whittaker et al, 2020). Other recent mycoprotein have focused on a single feedstock from agriculture/food production co-products or waste streams which is highly valuable but provides less flexibility than our model (Ritchie et al, 2017;Bulkan et al, 2020;Upcraft et al, 2021). Our model TEA developed a flexible and open access model with the ability to change feedstock composition as innovation occurs in the alternative protein space.…”
Section: Discussionmentioning
confidence: 99%
“…This level of investment suggests the need for a flexible technoeconomic model that examines the scaling of core production technologies and incorporates different biological factors and limitations, such as the specific growth rate of an organism. Other technoeconomic assessments (TEAs) have examined mycoprotein production from different perspectives including integration into a multi-product biorefinery and the use of agriculture waste streams as a fermentation substrate (Ritchie et al, 2017;Bulkan et al, 2020;Upcraft et al, 2021). Many TEAs utilize process simulation software that can require a significant economic investment and require additional training for effective use (AspenTech, 2022;Itelligen, Inc. 2022).…”
Section: Introductionmentioning
confidence: 99%
“…За технологічною складовою: відповідно до ДСТУ 4582:2006 «Система розроблення і поставлення продукції на виробництво». За економічною складовою: методи критичного аналізу й узагальнення інформації з наукових публікацій щодо оцінювання комерціалізації об'єктів інтелектуальної власності, ефективності реалізації бізнес-проєктів (Blanco-Gutiérrez et al, 2020;Bulkan et al, 2020;Menon et al, 2020;Омельяненко, 2012;Методики, б.д. ).…”
Section: мета і методи дослідженняunclassified
“…Для експертизи розроблених технологій застосовують різний методичний інструментарій, а саме технологічний аудит, GAP-і SWOT-аналіз (Blanco-Gutiérrez et al, 2020), методики LIFT, TAME™ (Bulkan et al, 2020), показники ефективності використання інвестицій (Menon et al, 2020).…”
Section: хлібнаunclassified
“…The authors reported that minimum calculated protein selling prices were determined to be price competitive with the selling prices of other plant‐based commercial products, as well as egg white and casein powders. Bulkan et al (2020) considered a TEA of producing mycoprotein from dried distiller's grains with solubles. The model considered two separate fungal species and created a dried fungal biomass product assumed to be sold at a comparable price to current mycoprotein products at about $4 per kg.…”
Section: Economics Of Cell‐cultivated Foodsmentioning
confidence: 99%